Penanaman nilai-nilai patriotisme melalui cerita sejarah perjuangan bangsa pada PAUD Sejahtera Tunggulwulung Kecamatan Lowokwaru Kota Malang - Bariyah, Khoirotul; Sari, Dyta Agnes Layung; Mukhlishin, Muh. Irfan (Penamas: Journal of Community Service, 2025)
The globalization era is accompanied by a massive influx of foreign cultures, resulting in the nation's noble values being easily eroded, exacerbated by the young generation's lack of understanding of the nation's historical struggles. At an early age, children experience a growth in high absorption capacity, which can have a lasting impact and remain throughout their lives. Therefore, instilling values of patriotism from an early age is highly relevant and urgent. The method employs a collaborative approach, focusing on inspiring stories about national heroes and historical events. This is chosen based on its suitability for the characteristics of early-age children who enjoy narrative and imagination at Sejahtera Tunggulwulung PAUD. This activity includes the introduction of national hero figures, inspirational stories about these heroes, accounts of historical events related to the nation's struggle, and singing national songs. The results show an increase in children's enthusiasm for historical stories, their ability to remember several important figures or events, and a rise in children's interest in national topics, as indicated by the questions about heroes. This activity successfully laid the foundation for instilling a sense of love for the homeland and pride in national identity in children.